Analisis Tingkat Kesehatan Bank Dengan Metode Camel Pada BMT Tumang Boyolali Cabang AndongTahun 2011-2013 - Hajjah, Fauzizah Nur; , Prof.Dr.H.M.Wahyudin,MS (2016)
This research with the title The Level of Bank Health Analyze with Camel Method at BMT Tumang Boyolali Andong Branch in 2011-2013. The purpose in this research knew how The Level of Bank Health at BMT Tumang Boyolali Andong Branch in 2011-2013. Data used quantitative data that was data measured in a numerik scale (number). The data source in this research use secondary data. Secondary data get obtained indirectly and in form of document, this data was consisted the L/R report and Balance report in 2011-2013. The data analyse method used quantitative analysis executed with searching ratio got by each factor, and then done research as according to component wight pursuant to specified Indonesia Bank. Ratio analyze was consisted of capital analyse, assessment relied on CAR (Capital Adequacy Ratio). Productive asset quality assessment at productive Asset classified to productive asset quality (KAP), reserve of Productive Asset Abolition Exclusion was which obliged to be formed by Bank ( PPAWPWB), Management consisted the management and risk public, Rentability consisted of the Return on Asset Ratio/ ROA and Earnings of Operational or Efficiency Ratio (BOPO), and liquidity consisted of the Cash ratio and Loan Deposit Ratio/LDR. Result of this research was Measurement mount the bank health at BMT Tumang Boyolali of Andong Branch from 2011 until 2013 by using CAMEL method covering capital, quality of asset, management, rentability and liquidity as a whole healthy.